Health and Income across the Life Cycle and Generations in Europe - Hans van Kippersluis; Tom van Ourti; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2008)
An age-cohort decomposition applied to panel data identifies how the mean, overall inequality and income-related inequality of self-assessed health evolve over the life cycle and differ across generations in 11 EU countries. There is a moderate and steady decline in mean health until the age of 70 or so and a steep acceleration in the rate of health deterioration beyond that age. In southern European countries and in Ireland, which have experienced the greatest changes in economic and social development, the average health of younger generations is significantly better than that of older generations. This is not observed in the northern European countries. In almost all countries, health is more dispersed among older generations indicating that Europe has experienced a reduction in overall health inequality over time. Although there is no consistent evidence that health inequality increases as a given cohort ages, this is true in the three largest countries – Britain, France and Germany. In the former two countries and the Netherlands, at least for males, the income gradient in health peaks around retirement age, as has been found for the US, but this pattern is not observed in the other countries. In most European countries, unlike the US, there is no evidence that income-related health inequality is greater among younger than older generations.
Keywords: D30; D31; I10; I12; 330; Health; Health inequality; Life cycle; Cohort; Gesundheit; Altersgruppe; Einkommensverteilung; Soziale Ungleichheit; Kohortenanalyse; EU-Staaten